Explicit Modeling of Solid Ocean Floor in Shallow Underwater Explosions - A.P. Walters; J.M. Didoszak; Y.W. Kwon (Shock and Vibration)
Current practices for modeling the ocean floor in underwater explosion simulations call for application of an inviscid fluid with soil properties. A method for modeling the ocean floor as a Lagrangian solid, vice an Eulerian fluid, was developed in order to determine its effects on underwater explosions in shallow water using the DYSMAS solver. The Lagrangian solid bottom model utilized transmitting boundary segments, exterior nodal forces acting as constraints, and the application of prestress to minimize any distortions into the fluid domain. For simplicity, elastic materials were used in this current effort, though multiple constitutive soil models can be applied to improve the overall accuracy of the model. Even though this method is unable to account for soil cratering effects, it does however provide the distinct advantage of modeling contoured ocean floors such as dredged channels and sloped bottoms absent in Eulerian formulations. The study conducted here showed significant differences among the initial bottom reflections for the different solid bottom contours that were modeled. The most important bottom contour effect was the distortion to the gas bubble and its associated first pulse timing. In addition to its utility in bottom modeling, implementation of the non-reflecting boundary along with realistic material models can be used to drastically reduce the size of current fluid domains.